ANALISIS IMPLEMENTASI SISTEM PENGENDALIAN INTERN PEMERINTAH DAN PENGARUHNYA TERHADAP PENGELOLAAN KEUANGAN DAERAH - Apriani, Dika Jaya; Irwansyah, Irwansyah; Baihaqi, Baihaqi (JURNAL FAIRNESS, 2013)
This research is quantitative research to exam of the implementation of Government Internal Control System (GICS) which include the control environment, risk assessment, control activities, information and communication, and monitoring of financial management. The research was conducted on the entire regional work units (40 SKPD) Bengkulu city government. Data obtained from questionnaires to 40 respondents, the toplevel officials at all on education. The results showed that the Government Internal Control System Implementation (GICS) includes control environment, risk assessment, control activities, information and communication, and monitoring simultaneously affect the financial management area. The better implementation of the GICS, the better financial management. GICS components partially proven positive effect on financial management is risk assessment, information and communication, and monitoring. The better the risk assessments conducted, information and communication systems are applied, and evaluation/ monitoring of implementation GICS good, the better the financial management area in Bengkulu city government on education.